PRODUK BANK SYARIAH SEBAGAI UPAYA UNTUK MENINGKATKAN LOYALITAS NASABAH KSPS PATI - Nailal Muna, Muhammad Afif; Kuncoro, Amin (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2016)
This study aimed to test the loyalty of KSPS customers by maximizing the product of sharia banks. It used descriptive quantitative research to collect primary data as the data source. The populations of this study were all KSPS clients, while the sample collection technique used non-probability sampling with accidental sampling type, so the respondents were 100 active customers. The results of this study showed that the products of sharia banks are able to give contribution to the customers’ loyalty in KSPS. Empirically,t-value is greater than t table and significant value is less than 5%. It proves that customers dare to give information to friends, especially if they would make a transaction, either saving or borrowing using the contract in accordance with Islam so it will bee free from usury things.